2020
DOI: 10.1021/acs.inorgchem.0c02680
|View full text |Cite
|
Sign up to set email alerts
|

Cubic Nanostructures of Nickel–Cobalt Carbonate Hydroxide Hydrate as a High-Performance Oxygen Evolution Reaction Electrocatalyst in Alkaline and Near-Neutral Media

Abstract: Catalyst development for the efficient direction of electrocatalytic water splitting with much less overpotential is crucial for meeting large-scale hydrogen generation. Being highly abundant and cost-effective, 3d transition-metal-based catalysts show promising activities in alkaline conditions. In this work, bimetallic nickel−cobalt carbonate hydroxide hydrate (NiCo-CHH) was prepared by a co-precipitation method with varying molar ratios of Ni/Co of 0.5:1, 1:1, and 1.5:1, which were analyzed for oxygen evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 66 publications
2
28
0
Order By: Relevance
“…The extra peak at 287.6 and 289.0 is ascribed to the carbon hydroxyl and C carbonate species, respectively. 34,35,37 Thus, these results suggest the main valence state of nickel−cobalt complex is Ni 2+ , Co 2+ , and Co 3+ , which is in good agreement with the previous report of the mixed nickel−cobalt carbonate hydroxide.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The extra peak at 287.6 and 289.0 is ascribed to the carbon hydroxyl and C carbonate species, respectively. 34,35,37 Thus, these results suggest the main valence state of nickel−cobalt complex is Ni 2+ , Co 2+ , and Co 3+ , which is in good agreement with the previous report of the mixed nickel−cobalt carbonate hydroxide.…”
Section: Resultssupporting
confidence: 93%
“…The deconvoluted C 1s spectra (Figure e) are also observed at 283.6 and 285.3 eV, corresponding with the characteristic binding energy of Ni carbonate and Co carbonate species, respectively. The extra peak at 287.6 and 289.0 is ascribed to the carbon hydroxyl and C carbonate species, respectively. ,, Thus, these results suggest the main valence state of nickel–cobalt complex is Ni 2+ , Co 2+ , and Co 3+ , which is in good agreement with the previous report of the mixed nickel–cobalt carbonate hydroxide.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Heretofore, various transition metal-based oxides, oxyhydroxides, nitrides, carbides, sulfides, and phosphides have been explored as catalysts for the overall water splitting. Among them, transition metal sulfides (TMSs) are more promising electrocatalysts for water splitting. However, a handful of articles reported that the TMSs’ inappropriate surface electronic structure negatively influences the OER and HER activity because of their weak adsorption of oxygen-containing intermediates.…”
Section: Introductionmentioning
confidence: 99%